Effect of Hot Compress Therapy with Sizi Powder Combined with Rehabilitation Training for Shoulder-hand Syndrome after Stroke - Mei LI; Lechang ZHAN; Ruihuan PAN; Leying ZHU; Hongxia CHEN (康复学报)
Objective:To observe the effect of hot compress therapy with Sizi Powder combined with rehabilitation training for shoulder-hand syndrome after stroke.Methods:A total of 70 patients with shoulder-hand syndrome after stroke were divided into observation group and control group according to the random number table method, with 35 cases in each group. Patients in the control group were treated with rehabilitation training, 30 minutes per time, 2 times a day, 6 days per week, and 2 weeks as a course of treatment. While patients in the observation group were given hot compress therapy with Sizi Powder, 10-20 minutes per time, once a day, 6 days per week, and 2 weeks as a course of treatment. Before and after treatment, the visual analog scale(VAS)for pain was used to evaluate the degree of pain, the Fugl-Meyer motor function scale for upper limb(FMA-U)and shoulder mobility were used to evaluate the upper limb function, and the degree of hand swelling was also measured.Results:Before treatment, there was no significant difference in VAS score, FMA-U score, shoulder mobility and hand swelling between the two groups(P>0.05).After two weeks treatment, the VAS score, FMA-U score, shoulder mobility and hand swelling of the two groups were improved compared with those before treatment(P<0.05), the VAS score and hand swelling in the observation group were(4.06±1.56)and(16.39±1.82)mL respectively, which were better than those(5.33±1.61)and(17.92±2.11)mL respectively in the control group, the differences were statistically significant(P<0.05).The FMA-U score of the observation group was(19.91±16.08)and that of the control group was(15.57±15.41), and there was no significant difference between the two groups(P>0.05).After treatment, the shoulder flexion was(52.00±40.93)°, the shoulder extension was(20.25±11.85)°, and the shoulder abduction was(48.28±31.95)°in the observation group, and those of the control group were(49.45±41.67)°, (18.22±11.68)°and(45.37±28.19)°respectively, there was no significant difference between the two groups(P>0.05).Conclusion:The hot compress therapy with Sizi Powder combined with rehabilitation training can alleviate the pain and reduce the degree of hand swelling in patients with shoulder-hand syndrome after stroke, and the curative effect is better than the simple rehabilitation training.